Interactive effects of porcine somatotropin and the beta-agonist salbutamol on growth and carcass criteria of three genotypes of swine - J A Hansen; J T Yen; J A Nienaber; T L Wheeler; J Klindt; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1992)
The objective of this research was to examine the interactive effects of porcine somatotropin (pST) and the beta-agonist salbutamol on the growth and carcass characteristics of three genotypes of pigs differing in lean and fat deposition potential. Thirty-two pigs each of either 1/4 Duroc-3/4 white composite (Duroc crossbred), purebred Meishan, or 1/4 Meishan-3/4 white composite (Meishan crossbred) breeding were injected daily with 0 or 4 mg pST and fed a diet containing 0 or 2.75 ppm salbutamol for approximately 34 d and subsequently slaughtered. As the percentage Meishan in the genotype increased, loin muscle area, semitendinosus weight, average daily gain (ADG), and carcass gain decreased. There was an interaction between salbutamol and genotype for ADG, daily protein gain, and total carcass gain, resulting in Meishan crossbred pigs having similar rates to non-treated Duroc crossbred pigs. When Duroc crossbred pigs were treated with salbutamol, both daily protein gain and total carcass gain were greatest, whereas ADG was nonsignificantly greater than that of untreated Duroc crossbred and salbutamol-treated Meishan crossbred pigs. Meishan pigs did not respond to salbutamol treatment for the criteria mentioned. Both pST and salbutamol increased loin muscle area and semitendinosus weight across genotypes. Leaf fat was reduced more by pST treatment in purebred Meishan pigs than in the other two genotypes, and salbutamol treatment resulted in small reductions in leaf fat across genotypes. Efficiency of feed utilization was similar among genotypes but increased with either pST or salbutamol treatment. The results of this research indicate that porcine somatotropin and the beta-agonist salbutamol have additive effects on the growth and carcass criteria of pigs. However, both growth modifiers appear to have differing degrees of response in different genotypes of swine.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; G-F; Performance; Carcass; Repartitioning; Hormone